Enhancing water quality and well-being of Penaeus vannamei (Boone, 1931) in Inland saline systems using mixed biochar amendments - Newmei Tachangliu; Vidya S. Bharti; Chalungal T. Amal; Tao Kara; Saurav Kumar; Pankaj Kumar; A. K. Verma; Arun Konduri; Swaraj Adakney; Shamika Sawant (Scientific Reports)
Abstract An experiment was conducted for 60 days in a 500L capacity FRP tank containing inland ground saline water (fortified to a level of 50% potassium) with one control (sediment) and three treatments; T1(Paddy Straw Biochar (PSB) in sediment), T2 (Banana Peduncle Biochar (BPB) in sediment), and T3 (PSB + BPB in sediment). Biochar (100 g) was amended with sediment (25 kg) at 9 tons/ha. Shrimps of average weight 5 ± 0.03 g were stocked at 60 juveniles/m3 and were fed at satiation levels using commercially available feed. Compared to control, in biochar contained treatments the ammonia levels were reduced, the pH, alkalinity, calcium-magnesium ratio, and potassium in water, were increased significantly. Growth metrics reveal a significant increase in final body weight, weight gain percentage, PER, HPSI, SGR, and reduced FCR (within 1–1.26) in biochar-treated groups with the highest survivability (92%) was observed in T3, which is mixed biochar amended sediment. At the end of the experiment, shrimp organs (hepatopancreas, gills, and muscles) and serum were sampled for tissue enzymes and serum profiles, respectively. The mean levels of lipase, amylase and protease varied significantly, and in biochar treated groups significant reduction in the activities of oxidative stress enzymes (SOD and CAT in Hepatopancreas) were recorded in comparison to control. For the serum, higher hemocyanin (0.33 ± 0.01mMolL-1) was observed in mixed biochar amended treatment (T3) and the least in control. In addition, the glucose level in the serum was significantly dropped in biochar-amended groups indicating reduced stress levels, while it increased in control. T3 was found to be the best, among all, in improving growth performance and maintaining the water quality. Even though biochar-amended treatments demonstrated positive outcomes regarding inland saline water quality, growth metrics, and well-being of the P. vannamei compared to control, a deeper analysis is necessary to understand the underlying mechanisms determining these beneficial effects of biochar.